Drosophila (Sophophora) carrolli n. sp., a new species from Brunei, closely related to Drosophila (Sophophora) rhopaloa Bock & Wheeler, 1972 (Diptera: Drosophilidae) - Gompel, Nicolas; Kopp, Artyom (Zootaxa, 2018)
We describe a new species in the Drosophila melanogaster species group, Drosophila carrolli n. sp., showing morphological affinities with D. rhopaloa Bock & Wheeler, 1972.